PENGARUH PENGGUNAAN MEDIA NEARPOD TERHADAP PEMAHAMAN MATERI IPA GERAK BENDA PADA SISWA KELAS 3 SDN PADELEGAN 1 - Uswatun Hasanah; Jamilah; Sukitman, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the impact of Nearpod as an instructional medium on third-grade students’ understanding of object motion. Utilizing a quasi-experimental design with a pretest-posttest control group, this study involved 40 students from SDN Padelegan 1, divided into an experimental group utilizing Nearpod and a control group employing traditional teaching methods. Data were gathered through pretest-posttest assessments and classroom observations. The findings indicate reveal a significant difference in posttest scores, with the experimental group scoring higher (M = 85.50, SD = 2.52) than the control group (M = 72.00, SD = 2.00). N-Gain analysis classified the experimental group’s improvement as high (0.684), while the control group remained in the moderate category (0.406). An independent t-test (t = 13.05, p < 0.001) confirmed that Nearpod significantly enhanced students’ conceptual understanding. Nearpod’s interactive features helped students visualize abstract concepts, increase engagement, and improve learning effectiveness in elementary science education. This study supports the integration of Nearpod in classrooms to optimize learning outcomes. Further research should explore its effectiveness in other subjects and its long-term impact on students' comprehension.